Healthcare professionals' perceptions about interprofessional teamwork: a national survey within Swedish child healthcare services - Ulrika Svea Nygren; Ylva Tindberg; Leif Eriksson; Ulf Larsson; Håkan Sandberg; Lena Nordgren (BMC, 2021)
Abstract Background Globally, interprofessional teamwork is described as a key method to promote health and prevent illness in children, namely, to achieve the goals of Child Healthcare Services (CHS). However, how teamwork should be designed within CHS to achieve the goals is unclear. This study aimed to investigate healthcare professionals' perceptions about 1) taking part in interprofessional teamwork, 2) team characteristics, and 3) whether the perceptions were related to professional affiliation or workplace. Methods A national cross-sectional survey was conducted using a web-based study-specific questionnaire sent to all accessible nurses, physicians, and psychologists in Swedish CHS (n = 3552). The response rate was 31.5%. To identify possible associations, logistic regressions were conducted. Results Almost all respondents, 1096/1119 (97.9%), reported taking part in some type of interprofessional teamwork within the Swedish CHS. Among those, the most common was team-based visits (82.2%). It was perceived that performing team-based visits resulted in fulfilled goals, expertise exceeding individual team members' competences, provision of high-quality care, and meeting children's and families' needs, to a greater extent, than if not performing team-based visits. Correspondingly, working as a team in parental groups was perceived as resulting in fulfilled goals, meeting the needs of children and their families, and continuity within the team to a greater extent than if not working together in a team. Professional affiliation was associated with different perceptions and types of teamwork. Family Centers were positively associated with all types of teamwork as well as continuity within the team. Conclusions Healthcare professionals' perceptions about team characteristics were associated with professional affiliation, workplace, and type of teamwork (defined as team activities) within the CHS. Professionals within Swedish CHS, taking part in team-based visits and in interprofessional teamwork in parental groups, perceived that the team fulfilled its goals and met the needs of children and families to a greater extent than professionals not taking part in these types of teamwork. Professionals at Family Centers were more likely to work in teams in different ways. Knowledge about interprofessional teamwork for individuals and groups in Swedish CHS might also be valuable in other healthcare settings, dealing with complex needs.